Revitalizing traditional crafts: How innovation and branding capability drive business success in batik SMEs - Zainurrafiqi, Zainurrafiqi; Saifi, Muhammad; Kusumawati, Andriani; Sunarti, Sunarti (Edelweiss Applied Science and Technology, 2025)
The increasingly competitive landscape of the batik industry, particularly in Madura, necessitates a strategic emphasis on innovation and branding capability to improve business performance. This study investigates the influence of innovation capability, branding capability, and competitive advantage on the business performance of medium-sized batik enterprises in Madura. The research surveyed 200 business owners and managers from medium-sized batik enterprises across four Madura regencies: Sumenep, Pamekasan, Sampang, and Bangkalan. Utilizing a census sampling method, data collection was conducted and analyzed using WarpPLS version 7. The findings reveal that innovation capability exerts a positive and significant impact on branding capability, competitive advantage, and business performance. Similarly, branding capability positively and significantly affects competitive advantage, although its effect on business performance is not significant. Competitive advantage, however, positively and significantly influences business performance. These results underscore the critical role of innovation and competitive positioning in enhancing the performance of medium-sized batik enterprises in Madura. The study suggests that business owners should focus on fostering innovation and leveraging competitive advantage as pivotal strategies for achieving sustainable business growth and long-term success. This insight provides valuable implications for practitioners aiming to thrive in the dynamic batik industry.